DAMPAK PERUBAHAN IKLIM TERHADAP PETANI TAMBAK GARAM DI KABUPATEN SAMPANG DAN SUMENEP - Kurniawan, Tikkyrino; Azizi, Achmad (P2KK LIPI, 2012)
The Ministry of Marine Affairs and Fisheries (MMAF) has proclaimed Salt Self-Suficiency since 2011 and established Salt Producing Community Empowerment Program (PUGAR) under the Directorate General of Coastal Marine and Small Islands (KP3K) to support it. This article was based on a research conducted in Sampang and Sumenep Districts from February to August 2012. Data was collected by using purposive sampling and analysed by descriptive method. Climate gives huge contribution to salt production because the process uses evaporation techniques onto salt ponds that depends on the weather and climate. Rainfall is one of the decreased of elements that influence salt production. The research shows that without an adaptation strategy, the rain might cause significant reduction in salt production. In addition, strong winds and hurricanes destroy the indmills and salt warehouses; tide high waves damages the ponds; and soil abrasion will reduce the number of salt ponds. This research recommends an adaptation strategy based on the knowledge about climate that can be used to forecast the volume of salt import and to determine the time frame and the amount of PUGAR needed. Keywords: climate impact, salt farmers, dry season, forecasting, adaptation strategy.